Wind Tunnels - Okamoto, Satoru (IntechOpen, 2011)
Although great advances in computational methods have been made in recent years, wind tunnel tests remain essential for obtaining the full range of data required to guide detailed design decisions for various practical engineering problems. This book collects original and innovative research studies on recent applications in wind tunnel tests, exhibiting various investigation directions and providing a birdâ€™s eye view on this broad subject area. It is composed of seven chapters that have been grouped in two major parts. The first part of the book (chapters 1â€"4) deals with wind tunnel technologies and devices. The second part (chapters 5â€"7) deals with the latest applications of wind tunnel testing. The text is addressed not only to researchers but also to professional engineers, engineering lecturers, and students seeking to gain better understanding of the current status of wind tunnels.ã€€Through its seven chapters, the reader will have an access to a wide range of works related to wind tunnel testing.